Unexpected Summation

Calculus Level 5

0 e x 2 x cos x d x \large \int_0^\infty e^{-x^2}x\cos x \ dx

If the above integral can be represented in the form n = 0 ( a ) n ( b n ) ! c ( d n ) ! {\displaystyle \sum_{n=0}^\infty \frac{(a)^n (bn)!}{c(dn)!}} , where a a , b b , c c and d d are integers, find a + b + c + d a + b + c + d .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mrudul Aluri
Jul 10, 2017

0 e x 2 x c o s x d x \large \int_{0}^{\infty}{e^{-x^2}}xcosx dx \\ let x 2 = u d u 2 = x d x 0 e u c o s u d u 2 From taylor series expansion of cosine function, we get - 1 2 0 e u n = 0 ( 1 ) n ( u ) 2 n ( 2 n ) ! d u 1 2 n = 0 ( 1 ) n ( 2 n ) ! 0 e u u n d u The above integral is of the form - Γ ( s + 1 ) = 0 e x x s d x = ( s ) ! 1 2 n = 0 ( 1 ) n ( 2 n ) ! 0 e u u n d u = 1 2 n = 0 ( 1 ) n ( 2 n ) ! n ! = n = 0 ( 1 ) n n ! 2 ( 2 n ) ! , a = 1 , b = 1 , c = 2 a n d d = 2 a + b + c + d = 4 \ \small \displaystyle \color{#3D99F6}\text{let } x^{2} = u \implies \frac{du}{2} = x dx \\ \implies \displaystyle \int_{0}^{\infty}{e^{-\color{#3D99F6}u}cos{\sqrt{u}}} \frac{du}{2} \\ \text{From taylor series expansion of cosine function, we get -} \\ \implies \displaystyle \frac12 \int_{0}^{\infty}{e^{-u}}\displaystyle {\color{#3D99F6}\sum_{n=0}^\infty \frac{(-1)^{n} (\sqrt{u})^{2n}}{(2n)!}} du \\ \implies {\displaystyle \frac12 {\sum_{n=0}^\infty \frac{(-1)^n}{(2n)!}} \int_{0}^{\infty}{e^{-u}}u^n du} \\ \text{The above integral is of the form - } \displaystyle{\Gamma(s+1) = \int_0^\infty e^{-x}x^{s}dx = (s)!} \\ \implies {\displaystyle \frac12 \sum_{n=0}^\infty \frac{(-1)^n}{(2n)!} {\color{#3D99F6} \int_{0}^{\infty}{e^{-u}}u^n du}} = \displaystyle \frac12 \sum_{n=0}^\infty \frac{(-1)^n}{(2n)!}{\color{#3D99F6}n!} \\ = \boxed{\displaystyle \sum_{n=0}^\infty \frac{(-1)^n n!}{2(2n)!}}, \implies a=-1,\ b=1, \ c=2 \ and \ d=2 \\ \implies a \ + \ b \ + \ c \ + \ d = \boxed{4}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...